Strategies to overcome HIV drug resistance-current and future perspectives - Temereanca, Aura; Ruta, Simona (Frontiers in Microbiology, 2023)
The availability of combined antiretroviral therapy (cART) has revolutionized the course of HIV infection, suppressing HIV viremia, restoring the immune system, and improving the quality of life of HIV infected patients. However, the emergence of drug resistant and multidrug resistant strains remains an important contributor to cART failure, associated with a higher risk of HIV-disease progression and mortality. According to the latest WHO HIV Drug Resistance Report, the prevalence of acquired and transmitted HIV drug resistance in ART naive individuals has exponentially increased in the recent years, being an important obstacle in ending HIV-1 epidemic as a public health threat by 2030. The prevalence of three and four-class resistance is estimated to range from 5% to 10% in Europe and less than 3% in North America. The new drug development strategies are focused on improved safety and resistance profile within the existing antiretroviral classes, discovery of drugs with novel mechanisms of action (e.g. attachment/post-attachment inhibitors, capsid inhibitors, maturation inhibitors, nucleoside reverse transcriptase translocation inhibitors), combination therapies with improved adherence, and treatment simplification with infrequent dosing. This review highlight the current progress in the management of salvage therapy for patients with multidrug-resistant HIV-1 infection, discussing the recently approved and under development antiretroviral agents, as well as the new drug targets that are providing a new avenue for the development of therapeutic interventions in HIV infection.